Global jihad: a brief history - Robinson, Glenn E. (Stanford University Press, 2021)
Klappentext: Most violent jihadi movements in the twentieth century focused on removing corrupt, repressive secular regimes throughout the Muslim world. But following the 1979 Soviet invasion of Afghanistan, a new form of jihadism emerged - global jihad - turning to the international arena as the primary locus of ideology and action. With this book, Glenn E. Robinson develops a compelling and provocative argument about this violent political movement's evolution. Global Jihad tells the story of four distinct jihadi waves, each with its own program for achieving a global end: whether a Jihadi International to liberate Muslim lands from foreign occupation; al-Qa'ida's call to drive the United States out of the Muslim world; ISIS using "jihadi cool" to recruit followers; or leaderless efforts of stochastic terror to "keep the dream alive." Robinson connects the rise of global jihad to other "movements of rage" such as the Nazi Brownshirts, White supremacists, Khmer Rouge, and Boko Haram. Ultimately, he shows that while global jihad has posed a low strategic threat, it has instigated an outsized reaction from the United States and other Western nations.